Funnel control for electrical circuits. Issue 1 (December 2014) - Berger, Thomas; Reis, Timo
Abstract We study the zero dynamics and funnel control for linear passive electrical circuits. We show that asymptotic stability of the zero dynamics can be characterized by criteria on the circuit topology. Thereafter we consider the output regulation problem for electrical circuits by funnel control. We show that for circuits with asymptotically stable zero dynamics, the funnel controller achieves tracking of a class of reference signals within a pre‐specified funnel. This result can be relaxed to the case of non‐autonomous zero dynamics by requiring the reference trajectory to evolve within a certain subspace. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)